Implementation of a Service-Learning Project Focused on Handwashing and Vaccinations Within an Undergraduate Microbiology Laboratory Course - Potter, Beth A. (Frontiers in Microbiology, 2021)
Two relevant topics in keeping populations healthy are handwashing and vaccinations. Thus, the service learning project titled “We Are Healthy” campaign was introduced within a microbiology laboratory course with two objectives; our biologists would better understand the importance of these actions by designing activities that engage the student community and to obtain an understanding of the campus community’s behaviors and beliefs concerning these topics. Students designed the campaign to include handwashing stations, pictures of bacterial cultures from swabbing common surfaces, trivia questions testing their peers’ knowledge of various vaccines, as well as handwashing and vaccination surveys. To assess the impact of the campaign on microbiology students (n=34), they were provided 10 questions that were scored on a scale from 1-5 (1=strongly disagree, 5=strongly agree). Student gains (score ˃ 3) were reported for depth in knowledge, development of better public speaking skills and a greater respect for volunteers suggesting that the campaign was beneficial. This study subsequently led to receiving grants to continue the campaign within the course, securing funding for handwashing and hand sanitizing stations, and initiating new undergraduate research projects.